New species of the genus Otitoma Jousseaume, 1898 (Pseudomelatomidae, Conoidea) from the Western Pacific Ocean - Morassi, Mauro; Nappo, Andrea; Bonfitto, Antonio (European Journal of Taxonomy, 2017)
Twelve new species are assigned to the genus Otitoma Jousseaume, 1898 in the family Pseudomelatomidae Morrison, 1966 and herein described: O. hadra sp. nov., O. neocaledonica sp. nov., O. rubiginostoma sp. nov and O. tropispira sp. nov. from New Caledonia; O. boucheti sp. nov., O. nereidum sp. nov. and O. sororcula sp. nov. from the Fiji Islands; O. xantholineata sp. nov. from the Solomon to the Fiji Islands; O. crassivaricosa sp. nov. from Fiji to Hiva Oa Island (Marquesas Archipelago); O. philpoppei sp. nov. from the Philippines but also reported from the Fiji Islands; O. elegans sp. nov. from the Fiji Islands and O. philippinensis sp. nov. from the Philippines. New data on O. carnicolor (Hervier, 1896) are provided. Otitoma mitra (Kilburn, 1986), from Southern Mozambique, is here considered a synonym of O. cyclophora (Deshayes, 1863). Drillia batjanensis Schepman, 1913, previously assigned to the genus Maoritomella Powell, 1942 in the family Borsoniidae Bellardi, 1875, is here assigned to the genus Otitoma. Photographs of the holotype of Drillia batjanensis are provided for the first time. In addition, color photographs of the type specimens of the following species are provided: Drillia kwandangensis Schepman, 1913, D. timorensis Schepman, 1913 and Mitrellatoma mitra Kilburn, 1986.